A Closer Look at Random and Fixed Effects Panel Regression in Structural Equation Modeling Using Lavaan. Issue 3 (4th May 2022) - Andersen, Henrik Kenneth
ABSTRACT: This article provides an in-depth look at random and fixed effects panel regression in the structural equation modeling (SEM) framework, as well as their application in the lavaan package for R. It is meant as an applied guide for researchers, covering the underlying model specification, syntax, and summary output.